Piper betle combination with ah plus and bioroot rcs: physicochemical,cytotoxic and antibacterial properties - Qi, Chen Wei (2023)
Exploration in endodontic material and procedure had been made to maximise the elimination of the microorganisms in the root canal system to improve the treatment success rate. Physicochemical and antibacterial properties are important in producing a novel endodontic sealer. Antibiotic resistance can cause a global health crisis if we use them inappropriately hence alternative is needed. Piper betle (PB) is one possible medicinal herb to be used for its effective antibacterial properties against Enterococcus faecalis (E. faecalis). Therefore, this study aims to investigate physicochemical properties (pH and solubility), cytotoxicity, and antibacterial effects of ethanolic extract of PB in combination with AH Plus (AH) and BioRoot RCS (BR) and sealers alone. Four tested materials were used; AH; PB and AH plus (PBAH); BR; and PB and BioRoot RCS (PBBR). pH testing was conducted for fresh and set sample for a period from immediate up to 4 weeks. Solubility test was in alignment with the International Standards Organization (ISO) method. At 24, 48, and 72 hours, MTT assay on HPdLF was performed to measure the cytotoxicity. Antibacterial effect was evaluated with modified direct contact test (MDCT) against E. faecalis at fresh, day- 1-set and day-7-set state of the tested materials. Data were analysed with SPSS version 25 with Tukey’s post-test at the level of significance of P = 0.05. In fresh state, PB increase the alkalinity of AH at significant level (P = 0.000) after 2 hours. BR and PBBR demonstrated significantly high (P = 0.000) alkaline value at all time points, without significant difference with presence of PB. For set sample, PB decrease the pH value of BR while increase the pH value of AH. PBBR showed significant reduction in solubility as compared to BR, AH and PBAH showed no significant difference. Besides, PBAH showed significant decrease in cytotoxicity at 48 hours as compared to AH (45.20%, 18.85%). PB reduce the antibacterial effect of BR at all times at significant level (P = 0.000, 0.014, 0.032). Conclusion, PBAH has higher pH value than AH at fresh state, while PBBR has lower pH value than BR when set. PBBR has significant lower solubility than BR. PBAH has significant reduced cytotoxicity as compared to AH on HPdLF at 48 hours. PBBR was cytotoxic to HPdLF at 24 and 48 hours. Both AH and PBAH exhibited antibacterial property against E. faecalis, followed by BR and PBBR. In conclusion, PBAH is a potential enhanced root canal sealer and may be further studied to fully elicit its profound properties.